(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To assess sleep quality and identify associated factors among outpatients with hypertension. Methods: A cross-sectional descriptive study was conducted among 298 hypertensive outpatients in 2025. Data were collected using a structured questionnaire and the PSQI. Poor sleep quality was defined as a PSQI score greater than 5. Multivariable logistic regression analysis was performed to identify factors associated with poor sleep quality, with statistical significance set at p < 0.05. Results: The mean age of the study participants was 65.2 ± 9.6 years, with the majority being aged ≥ 60 years. The prevalence of poor sleep quality was 62.1%, and the mean PSQI score was 11.2 ± 5.4. Prolonged sleep latency and short sleep duration were common findings, and more than half of the patients experienced daytime dysfunction. Multivariable logistic regression analysis showed that age ≥ 70 years, duration of hypertension treatment longer than 5 years, use of six or more medications, coexisting cardiovascular disease, and musculoskeletal disorders were independently associated with poor sleep quality. Sex and diabetes mellitus were not significantly associated with poor sleep quality. Conclusion: Poor sleep quality is common among patients with hypertension.